2005
DOI: 10.1159/000083559
|View full text |Cite
|
Sign up to set email alerts
|

Use of α<sub>1</sub>-Blockers in Female Functional Bladder Neck Obstruction

Abstract: Introduction: Bladder outflow obstruction may cause obstructive or irritative symptoms. The diagnosis of female functional bladder neck obstruction requires a pressure/flow study and electromyography performed by videourodynamics. The treatment includes self-catheterization or bladder neck incision. We administered tamsulosin, an α1A/α1D-selective adrenergic antagonist, in women with functional bladder neck obstruction to evaluate its potential therapeutic effects. Patients andMethods: A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1
7

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 36 publications
(63 reference statements)
0
22
1
7
Order By: Relevance
“…The majority of patients accepted to continue therapy for more than 1 month indicating a lack of severe adverse effects and improvement in their symptomatology on the basis of the patients' perspective. These results are a little better than the improvement rates reported by Kumar et al [14] and Pischedda et al [15] . They reported significant improvement in symptoms, Q max and PVR in 50 and 56% of women with functional BOO.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…The majority of patients accepted to continue therapy for more than 1 month indicating a lack of severe adverse effects and improvement in their symptomatology on the basis of the patients' perspective. These results are a little better than the improvement rates reported by Kumar et al [14] and Pischedda et al [15] . They reported significant improvement in symptoms, Q max and PVR in 50 and 56% of women with functional BOO.…”
Section: Discussioncontrasting
confidence: 50%
“…Finally Yucel et al [8] reported their experience on 28 children with dysfunctional voiding and urinary retention concluding that ␣ -blocker therapy seems to be a viable alternative to biofeedback in this group of patients as it is well tolerated and improves bladder emptying. Kumar et al [14] , Pischedda et al [15] and more recently Kessler et al [2] reported significant improvement in symptoms and urodynamic parameters in women with functional BOO. The few data available from studies and experimental models in males agree on the rationale for ␣ -lithic agents as therapy for women with micturitional disturbances due to functional obstructive symptoms of the lower urinary tract.…”
Section: Discussionmentioning
confidence: 95%
“…Urodynamisch gezien leidde in alle prospectieve onderzoeken tamsulosine tot een significante verbetering van de Qmax met 3,3-7,1 ml/s, en in de studie waarin 1-5 mg terazosine werd gegeven zelfs met 11,1 ml/s [9][10][11][12][13][14]. De PdetQmax werd in twee prospectieve studies onderzocht en daalde in de ene studie met 10 cmH2O en in de andere studie met 20 cmH2O [13,14]. Het residu na mictie nam met circa een derde af, terwijl het mictievolume nagenoeg gelijk bleef.…”
Section: Resultatenunclassified
“…Pharmacologic strategies also have been used to address outlet resistance. α-Adrenoreceptor blockade with alfuzosin [20], terazosin [21], and tamsulosin [22] has been shown to lead to improvements in bladder emptying, quality of life, and lower urinary tract symptoms in women with VD. Although α-blockers have been used in men with bladder outlet obstruction for many years, their use in women has drawn interest only relatively recently.…”
Section: Should Urethral Dilatation Be An Effective Treatment?mentioning
confidence: 99%